2016
DOI: 10.1002/2015jb012497
|View full text |Cite
|
Sign up to set email alerts
|

Coseismic slip distribution of the 2015 Mw7.8 Gorkha, Nepal, earthquake from joint inversion of GPS and InSAR data for slip within a 3‐D heterogeneous Domain

Abstract: We derive a coseismic slip model of the 2015 Mw7.8 Gorkha earthquake on the basis of GPS and line‐of‐sight displacements from ALOS‐2 descending interferograms, using Green's functions calculated with a 3‐D finite element model (FEM). The FEM simulates a nonuniform distribution of elastic material properties and a precise geometric configuration of the irregular topographical surface. The rupturing fault is modeled as a low‐angle and north dipping surface within the Main Frontal Thrust along the convergent marg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 56 publications
1
39
0
Order By: Relevance
“…We calculate the postseismic transients of Δ p and ΔCFS at the VE hypocenter under a fully coupled poroelastic scheme, which is governed by a volumetric strain equation derived from mass conservation and Darcy's law (Wang, ): normalαϵkkt+Sϵpt=knormalμf2p where α is the Biot‐Willis coefficient; t indicates the elapsed time since the loading event (i.e., the AE); ϵ kk = ∂ u k /∂ x k is the volumetric strain and subscript k cycles through the orthogonal axis 1, 2, and 3; S ϵ is the constrained storage coefficient; and k is the intrinsic rock permeability; μ f is the pore fluid viscosity (Table S1 in the supporting information). It is also constrained by a force equilibrium equation (Detournay & Cheng, ; Tung & Masterlark, ; Wang & Kümpel, ): G2ui+G12v2ukxixk=αpxi where G and v respectively denote the shear modulus and Poisson's ratio which are determined by a local velocity model (Cirella et al, ). The Cartesian coordinates and corresponding displacements are denoted as x and u , respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We calculate the postseismic transients of Δ p and ΔCFS at the VE hypocenter under a fully coupled poroelastic scheme, which is governed by a volumetric strain equation derived from mass conservation and Darcy's law (Wang, ): normalαϵkkt+Sϵpt=knormalμf2p where α is the Biot‐Willis coefficient; t indicates the elapsed time since the loading event (i.e., the AE); ϵ kk = ∂ u k /∂ x k is the volumetric strain and subscript k cycles through the orthogonal axis 1, 2, and 3; S ϵ is the constrained storage coefficient; and k is the intrinsic rock permeability; μ f is the pore fluid viscosity (Table S1 in the supporting information). It is also constrained by a force equilibrium equation (Detournay & Cheng, ; Tung & Masterlark, ; Wang & Kümpel, ): G2ui+G12v2ukxixk=αpxi where G and v respectively denote the shear modulus and Poisson's ratio which are determined by a local velocity model (Cirella et al, ). The Cartesian coordinates and corresponding displacements are denoted as x and u , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…where α is the Biot-Willis coefficient; t indicates the elapsed time since the loading event (i.e., the AE); ϵ kk = ∂u k /∂x k is the volumetric strain and subscript k cycles through the orthogonal axis 1, 2, and 3; S ϵ is the constrained storage coefficient; and k is the intrinsic rock permeability; μ f is the pore fluid viscosity ( Table S1 in the supporting information). It is also constrained by a force equilibrium equation (Detournay & Cheng, 1993;Tung & Masterlark, 2016;Wang & Kümpel, 2003):…”
Section: Methodsmentioning
confidence: 99%
“…Finite element models (FEMs) are well suited to simulate both of the above tectonic complexities (Hughes et al, ; Kyriakopoulos et al, ; Figure ) and assimilate existing crustal information such as CRUST2.0 that cannot be well accommodated by rectangular fault patches in an analytical half‐space (Okada, ). The advantages of using FEMs over customary half‐space solutions have been exemplified in recent earthquakes and volcanic eruptions (Hughes et al, ; Kyriakopoulos et al, ; Masterlark, ; Masterlark et al, ; Masterlark et al, ; Masterlark & Hughes, ; Trasatti et al, ; Tung & Masterlark, , , ; Williams & Wallace, ), contributing to significantly more accurate source information. Yet, the lengthy processes of building FEMs and the corresponding Green's function (GF) matrix are the bottlenecks of real‐time analyses (c.f.…”
Section: Introductionmentioning
confidence: 99%
“…While such analytical solutions are computationally efficient, they overly simplify the mechanically complex structure of upper crust along plate margins (Bjarnason et al, ; Gutscher et al, )—a problem which translates to prediction errors for the seafloor deformation that drives tsunami genesis (Wei et al, ). A wide range of studies have already revealed the influence of subsurface rock heterogeneity in deriving coseismic rupture characteristics (Eleonora et al, ; Fernandez et al, ; He & Peltzer, ; He et al, ; Hughes et al, ; Jovanovich et al, ; Kyriakopoulos et al, ; Masterlark et al, ; Masterlark et al, ; Pan, ; Sato, ; Savage, , ; Trasatti et al, ; Tung & Masterlark, , ; Wang et al, ), when inverting the earthquake deformation recorded by GPS and interferometric synthetic aperture radar data. Therefore, we propose to investigate whether the distributed rock properties in deformational models might become significant enough to alter the predictions of seafloor deformation and subsequent tsunami behavior.…”
Section: Introductionmentioning
confidence: 99%